Clinical significance of small airway obstruction markers in patients with asthma. Issue 4 (April 2014) - Gonem, S.; Natarajan, S.; Desai, D.; Corkill, S.; Singapuri, A.; Bradding, P.; Gustafsson, P.; Costanza, R.; Kajekar, R.; Parmar, H.; Brightling, C. E.; Siddiqui, S.
Summary Background The role of small airway obstruction in the clinical expression of asthma is incompletely understood. Objective We tested the hypotheses that markers of small airway obstruction are associated with (i) increased asthma severity, (ii) impaired asthma control and quality of life and (iii) frequent exacerbations. Methods Seventy‐four adults with asthma and 18 healthy control subjects underwent impulse oscillometry (IOS), multiple breath inert gas washout (MBW), body plethysmography, single‐breath determination of carbon monoxide uptake and spirometry. Patients completed the six‐point Asthma Control Questionnaire (ACQ‐6) and standardized Asthma Quality of Life Questionnaire [AQLQ(S)]. Asthma severity was classified according to the Global Initiative for Asthma (GINA) treatment steps. Results The putative small airway obstruction markers Sacin, resistance at 5 Hz minus resistance at 20 Hz (R5‐R20) and reactance area (AX) were not independently associated with asthma severity, control, quality of life or exacerbations. In contrast, markers of total (R5) and mean airway resistance of large and small airways (R20) were significantly higher in the severe asthma group compared with the mild–moderate group (0.47 vs. 0.37, P < 0.05 for R5; 0.39 vs. 0.31, P < 0.01 for R20). The strongest independent contributors to ACQ‐6 score were R20 and forced expiratory volume in one second (% pred.), and the strongest independent contributors to AQLQ(S) score were R20 and forced vital capacity (% pred.). A history of one or more exacerbations within the previous year was independently associated with R20. Conclusions and Clinical Relevance Previously reported markers of small airway obstruction do not appear to be independently associated with asthma disease expression. In contrast, the IOS parameter R20, a marker of mean airway resistance of both large and small airways, appears to have independent clinical significance. These observations require confirmation in prospective longitudinal studies.